In Vitro Assessment of Antioxidant Activity, Total Phenolic and Flavonoid Contents of Sweet Marjoram (Origanum majorana L.) Extract - LAHRECHE, Talal; BRADAIE, Mohamed Lamine; HAMDI, Taha Mossadak (International journal of Horticulture, Agriculture and Food science, 2020)
Sweet marjoram (Origanum majorana L.) is cultivated as a condiment for its aromatic leaves for culinary purposes and utilized as a medicinal plant for many diseases. The aim of this study was to evaluate in vitro antioxidant activity of marjoram extract by the 2, 2–diphenyl–1–picrylhydrazyl–hydrate (DPPH) free radical scavenging method while total phenolic and flavonoid contents were quantified by spectrophotometry using Folin−Ciocalteu and aluminum chloride colorimetric methods, respectively. The extraction yield of sweet marjoram obtained by maceration in absolute ethanol at a ratio of 1/5 (w/v) for 24h at room temperature was 8.41 ± 0.76 % (w/w). The obtained results showed that the investigated extract contained a higher amount of phenolics: 164.96 ± 4.61 mg GAE/g of dry plant, lower flavonoid contents: 44.61 ± 2.08 mg QE/g of dry plant, and exhibited a strong antioxidant activity (IC50 value: 40.09 µg/ml) almost like those of the used standard products, namely ascorbic acid and butylated hydroxytoluene (BHT). Based on the obtained results, marjoram (Origanum majorana L.) features a potential application as natural antioxidants that could be exploited by the pharmaceutical and food industries.